2017
DOI: 10.1177/1559325817744945
|View full text |Cite
|
Sign up to set email alerts
|

Hormetic Response by Silver Nanoparticles on In Vitro Multiplication of Sugarcane (Saccharum spp. Cv. Mex 69-290) Using a Temporary Immersion System

Abstract: Background:Hormesis is considered a dose–response phenomenon characterized by growth stimulation at low doses and inhibition at high doses. The hormetic response by silver nanoparticles (AgNPs) on in vitro multiplication of sugarcane was evaluated using a temporary immersion system.Methods:Sugarcane shoots were used as explants cultured in Murashige and Skoog medium with AgNPs at concentrations of 0, 25, 50, 100, and 200 mg/L. Shoot multiplication rate and length were used to determine hormetic response. Total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 41 publications
3
53
0
1
Order By: Relevance
“…High doses of Ag-NPs, however, may block nutrient transportation by ionic channel competition and, reducing shoot number and length, induce phytotoxicity. Although achieved with differently functionalized NPs and in diverse plant models, Bello-Bello et al [ 29 ] reported comparable results with Sugarcane shoots treated with PVP-coated Ag-NPs under similar experimental conditions.…”
Section: Resultsmentioning
confidence: 93%
“…High doses of Ag-NPs, however, may block nutrient transportation by ionic channel competition and, reducing shoot number and length, induce phytotoxicity. Although achieved with differently functionalized NPs and in diverse plant models, Bello-Bello et al [ 29 ] reported comparable results with Sugarcane shoots treated with PVP-coated Ag-NPs under similar experimental conditions.…”
Section: Resultsmentioning
confidence: 93%
“…For onions, cytotoxic damage apparently begins with 100 µg/mL of AgNPs because only a small increase of malondialdehyde is observed ( Figure 5 c). While on the other plants, with this concentration, the damage is quite evident not only at the molecular level but also physiologically, due to different antioxidant response of these plants [ 50 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further, another study showed a remarkable increase in the chlorophyll content in Stevia rebaudiana after treatment with 25 mg L −1 AgNPs 26 . In general, the application of AgNPs reportedly increases the photosynthetic pigment amount in vanilla 32 and sugarcane 33 . The reason for the increased chlorophyll content in our study could be the increases in nitrogen, magnesium, and iron concentrations in the plant tissues treated with AgNPs, given that these elements are associated with chlorophyll biosynthesis 26 .…”
Section: Discussionmentioning
confidence: 95%